Avaliação da gerência de requisitos da cotic com base nível G do modelo MR-MPS-SW e proposição de métodos para adequação - RODES, Sérgio Ewerton Maciel (2019)
This work presents an evaluation of a software development institution regarding the requirements management process in conformance to the level G of the Brazilian reference model for software process improvement (MR-MPS-SW, in Portuguese). First, a survey of the whole process of collection and development of requirements was carried out. Later this process was compared to each expected result of MR-MPS-SW requirements management process, evidencing whether or not the processes performed at the institution meet the expected results in the reference model. After this evaluation, a proposal was made to adapt to the reference model, where for each expected result that the institution did not fit, a proposal of adhesion was drawn up without the use of a new tool or new technology, facilitating its application. All the proposals elaborated were based on the respect to the evaluated institution that uses agile methods.